Pengaruh Perkembangan Teknologi Informasi Terhadap Pembelajaran Bahasa Indonesia - Chairunnisa, Chairunnisa (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The development of information technology has brought significant changes in various aspects of life, including in the field of education. This paper aims to explore the influence of the development of information technology on Indonesian language learning for students of SMK Rahmatutthoyibah Tangerang. The method used by the researcher is the questionnaire method, namely research that aims to obtain more detailed information from a research object. In this study, the variable used is the dependent variable. The sample used by the author was 30 students of SMK Rahmatutthoyibah Tangerang. The research instrument used in this research process was a questionnaire instrument. This study identifies the positive impact of information technology on language learning, as well as the challenges that may be faced in implementing it. These findings are expected to provide deeper insight into how information technology can improve the effectiveness of Indonesian language learning in the digital era.